Penguatan Karakter dalam Manajemen Kelas: Strategi Efektif untuk Meningkatkan Kualitas Pendidikan dan Perkembangan Holistik Siswa - Arfa, Arman Man; Lasaiba, Djamila (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
This study explores the effectiveness of classroom management with a character education approach in enhancing the quality of the learning environment and the holistic development of students. Through a literature review method, various scholarly sources were analyzed to identify the impact of character education on classroom climate, student behavior, and the development of social and emotional skills. The research findings indicate that character education creates a more positive classroom climate, where students feel valued and supported, and significantly reduces negative behaviors such as aggression and bullying. Furthermore, this approach has proven effective in improving students' social and emotional skills, which are crucial for their academic success and long-term well-being. The long-term impact of character education is also evident in forming a strong moral identity and the readiness of students to become responsible citizens. Thus, classroom management based on character education is a comprehensive and effective strategy for supporting students' academic, social, and moral development, as well as preparing them to face future challenges with integrity and responsibility